Answer:
Simplifying
(-4x + -2) + -1(13x + 1) = 0
Reorder the terms:
(-2 + -4x) + -1(13x + 1) = 0
Remove parenthesis around (-2 + -4x)
-2 + -4x + -1(13x + 1) = 0
Reorder the terms:
-2 + -4x + -1(1 + 13x) = 0
-2 + -4x + (1 * -1 + 13x * -1) = 0
-2 + -4x + (-1 + -13x) = 0
Reorder the terms:
-2 + -1 + -4x + -13x = 0
Combine like terms: -2 + -1 = -3
-3 + -4x + -13x = 0
Combine like terms: -4x + -13x = -17x
-3 + -17x = 0
Solving
-3 + -17x = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '3' to each side of the equation.
-3 + 3 + -17x = 0 + 3
Combine like terms: -3 + 3 = 0
0 + -17x = 0 + 3
-17x = 0 + 3
Combine like terms: 0 + 3 = 3
-17x = 3
Divide each side by '-17'.
x = -0.1764705882
Simplifying
x = -0.1764705882